Hubungan Kepatuhan Minum Obat Amlodipin Dengan Kualitas Hidup Pasien Hipertensi Pada Dokter Praktik Perorangan Di Ranah Batahan Kabupaten Pasaman Baratabupaten Pasaman Barat - Barita Juliano Siregar; yardi; Sripi Mahalaya; Muhammad Rafly Syah Putra; Edi Rohaedi (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2025)
Hypertension is a disease in which a person has an increase in diastolic (≥90 mmHg) and systolic (≥140 mmHg) blood pressure. Treatment of hypertension is a long-term therapy, one of the parameters to achieve therapeutic success is patient compliance in taking medication in order to minimize the impact caused so that it can affect the quality of life of patients. The purpose of this study was to analyze the relationship between compliance with amlodipine consumption with the quality of life of hypertensive patients at Individual Practitioners in Ranah Batahan. The research design used was quantitative research using a cross- sectional approach conducted on 45 respondents who met the inclusion criteria. The level of compliance with taking the respondent's medication was measured using the Pill Count method and the quality of life of hypertensive patients using the WHOQOL questionnaire. Data were processed using IBM SPSS 22 and analyzed through frequency distribution analysis (univariate) and Chi square test (bivariate). Based on the results of measuring the level of compliance, 29 respondents (64.4%) were declared compliant and 16 respondents (35.6%) were not compliant. Measurement of quality of life level, as many as 28 (62.2%) were moderate and 17 (37.8%) were low. The conclusion of this study is that there is a significant relationship between the level of compliance with quality of life p value < 0.05 with moderate relationship strength p value 0.003.